Zakat as a Complementary Fiscal Instrument: Strengthening Amil Governance through a Multidisciplinary Islamic Perspective - Rizal, Sofyan; Kharisma, Dita (RSF Conference Series: Business, Management and Social Sciences, 2026)
Fiscal systems in many Muslim-majority countries are under growing strain as governments are expected to expand social protection, reduce inequality, and respond to economic uncertainty—often while relying on tax-based instruments that face structural and institutional limits. In this context, zakat is frequently acknowledged for its redistributive purpose; yet in practice, it is still treated mainly as a charitable activity or as a parallel system operating outside formal fiscal policy. This paper argues that such treatment underestimates the potential role of zakat within contemporary public finance. The study aims to reposition zakat as complementary fiscal instrument and to highlight the role of amil governance as a decisive factor in enabling this complementarity. Using a qualitative and conceptual approach—based on conceptual synthesis of peer-reviewed literature and institutional standards in zakat governance (including zakat supervision principles)—the analysis integrates Islamic jurisprudence, maqasid al-shari’ah, public finance theory, and governance perspectives to develop an integrated analytical framework. Rather than testing hypotheses or estimating fiscal impacts, the paper focuses on institutional reasoning and theory-building. The main contribution of this study lies in advancing a governance-centered framework that places amil institutions at the heart of zakat’s fiscal relevance. It demonstrates how accountability, transparency, and public trust—particularly in increasingly digitalized zakat systems—shape zakat’s capacity to operate alongside taxation. By shifting attention from fiscal outcomes to governance foundations, the paper offers a clear institutional pathway for strengthening zakat’s role within modern social protection and fiscal systems.